Higher education to tourism in Brazil: Analysis of the supply of higher education in Northeastern Brazil by the Federal Institutes. - Keila Cristina Nicolau Mota; Francisco Antonio dos Anjos (Revista Brasileira de Pesquisa em Turismo, 2012)
The context of post-industrial society is of great change, requiring more skills and causing an increase in quantity and quality of offering higher education courses in tourism and related areas in Brazil. This article, arising from doctoral research, aimed to analyze the higher education courses of tourism offered in Northeast Brazil by the Federal Institutes of Education, Science and Technology of the country, considering the context of Brazilian higher education. It also sought, among other specific goals, to map out the provision of higher education in tourism in Brazil. Characterized as descriptive and explanatory of the object, according to its objectives, the work involved research on the bibliographic, documental and field type. In the field, a survey was conducted with the Federal Institutes of the Northeast, researching and analyzing aspects of the education program and organizational curriculum, course objectives and professional profile of graduates, communication, relationships and quality of courses in tourism and related areas offered by them. Over a thousand higher education courses in tourism and related fields on offer in Brazil were identified in 2010, of which 251 are offered in the Northeast and only 13 of them are offered by IF. The courses prepare their projects based on the parameters of the MEC (92.30%), do not consider the qualification policy of the state where they are located, offer up three foreign languages and seek to train primarily planning and project design, differentiate itself from the bachelor’s degrees in a more practical and operational focus of the course and not for research. The research intended to be a tool to promote discussion on the topic, and may subsidize academic studies and practical actions for educational administrators and policy makers in Brazil, mainly in the Northeast.